(untitled) (Economics and region, 2022)
It has been established that in modern economic conditions the role of innovation activity for domestic enterprises is becoming increasingly important. In order to increase the efficiency of development and implementation of innovative projects in the enterprise, it’s necessary to apply innovation marketing. It has been found that innovation marketing provides an opportunity, first of all, to identify unmet consumer needs and to develop appropriate elements of the marketing complex to adapt the created innovative product to market requirements and to promote it further. It has been established that, in general, the effectiveness of innovative activity depends on the qualifications of the company’s employees. The process of formation of personnel policy in the enterprise in modern conditions was studied. The features of effective personnel policy formation were considered and analyzed. The main factors influencing the process of personnel policy formation in the enterprise were also defined.